André-Louis Cholesky Mathematician, Topographer and Army Officer - Brezinski, Claude; Tournès, Dominique; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Birkhäuser, 2014)
Outside the professional circles of topography and applied mathematics, the life and work of André-Louis Cholesky (1875–1918) are still relatively unknown to the scientific community. This new book appreciably widens the exposure of his remarkable personal achievements in topography and mathematics to a much larger international audience. Cholesky is also interesting to historians because he is a perfect representative of the "scientists engineers" that, since the early 19th century, had issued from the French scientific high schools. Because they had received a high level of mathematical education, they were able to innovate in their practice of engineering. In the case of Cholesky, this resulted in original contributions in artillery, topography, numerical analysis and graphical calculation. In addition, the book places his education and works within the history of several European countries through the 17th to 19th centuries. The book begins with Cholesky's biography, followed by his family’s history and an introduction to topography. It continues with a historical analysis of an unpublished paper (translated into English) in which Cholesky explained his method for linear systems. Cholesky's other works are then described, such as his participation in teaching at a superior "school by correspondence" founded by Léon Eyrolles. His important unpublished book in French on graphical calculation, which is reproduced in its entirety, is analyzed in detail and compared to similar contemporary publications. The biography of Ernest Benoit, who wrote the first paper on Cholesky's method, is provided. Various documents, highlighting the life and the personality of Cholesky, round out his story and end the book.
Preface -- Biography of Cholesky -- Cholesky's family -- On topography -- The method of Cholesky for linear systems -- Other works of Cholesky -- Léon Eyrolles and his superior school -- An unpublished book by Cholesky -- Ernest Benoît -- Documents -- Acknowledgments -- Bibliography -- Index.
Keywords: Mathematics; History; Applied mathematics; Engineering mathematics; Computer mathematics; History of Mathematical Sciences; Applications of Mathematics; Computational Mathematics and Numerical Analysis